Experimental investigations of thermomechanical couplings in TiNi shape-memory alloy during a torsion-tension (compression) test - Oliferuk, W. (Archives of Mechanics, 1999)
Experimental investigations of thermomechanical coupling in TiNi alloy during uniaxial and biaxial loading at the temperature higher than the room temperature is presented. The applied method is based on contactless temperature measurements. The results of the investigations are reported. They are interpreted in terms of the phase transitions.